Do Recycled Cotton or Polyester Fibers Influence the Shedding Propensity of Fabrics during Laundering?. (January 2020) - Frost, H.; Zambrano, M. C.; Leonas, K.; Pawlak, J. J.; Venditti, R. A.
Fabric shedding during laundering is detrimental to the longevity of clothing textiles, and in the case of non-biodegradable, synthetic fabrics, it is a source of diffuse microplastic fiber pollution. Textile recycling offers numerous economic and environmental benefits; however differences in fabric shedding due to their recycled fiber contents are relatively unknown. Accelerated laundering experiments were conducted to quantify the shedding propensity and characteristics of cotton knit, polyester knit, and twill weave fabrics, each at three differing recycled fiber contents. The 70% recycled polyester shed significantly fewer microfibers than the 40% recycled polyester. No other significant influences of recycled fiber content on shedding propensity were identified. The mean length of shed fibers from the 70% recycled polyester was significantly higher than that of the virgin polyester and the 40% recycled polyester.